2022
DOI: 10.3390/cells11050789
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Biomarkers and Blood-Brain Barrier Integrity in Preeclampsia

Abstract: Cerebral complications in preeclampsia contribute substantially to maternal mortality and morbidity. There is a lack of reliable and accessible predictors for preeclampsia-related cerebral complications. In this study, plasma from women with preeclampsia (n = 28), women with normal pregnancies (n = 28) and non-pregnant women (n = 16) was analyzed for concentrations of the cerebral biomarkers neurofilament light (NfL), tau, neuron-specific enolase (NSE) and S100B. Then, an in vitro blood–brain barrier (BBB) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Other studies that have assessed markers of neuronal injury or neuroinflammation in women with preeclampsia or eclampsia during pregnancy have shown increased pro-inflammatory cytokines in cerebrospinal fluid from preeclampsia and eclampsia patients compared to normal pregnant women (Bergman et al, 2021b). Increased plasma concentration of different markers of glial or neuronal damage were found in women with preeclampsia compared to normal pregnant women (Friis et al, 2022). Taken together, clinical and preclinical studies demonstrate increased BBB permeability in preeclampsia with evidence of involvement of extracellular vesicles, pro-inflammatory cytokines, and other factors during pregnancy.…”
Section: Potential Mechanisms Contributing To Increased Risk Of Cereb...mentioning
confidence: 93%
“…Other studies that have assessed markers of neuronal injury or neuroinflammation in women with preeclampsia or eclampsia during pregnancy have shown increased pro-inflammatory cytokines in cerebrospinal fluid from preeclampsia and eclampsia patients compared to normal pregnant women (Bergman et al, 2021b). Increased plasma concentration of different markers of glial or neuronal damage were found in women with preeclampsia compared to normal pregnant women (Friis et al, 2022). Taken together, clinical and preclinical studies demonstrate increased BBB permeability in preeclampsia with evidence of involvement of extracellular vesicles, pro-inflammatory cytokines, and other factors during pregnancy.…”
Section: Potential Mechanisms Contributing To Increased Risk Of Cereb...mentioning
confidence: 93%
“…Cerebral biomarkers for neurological injury in dementia include neurofilament light and tau found in axons, as well as neuron-specific enolase and S100B found in glial cells ( Friis et al, 2022 ). Recent studies investigated whether these cerebral biomarkers for neurological injury were present in cases of preeclampsia and the findings were inconsistent.…”
Section: Cerebral Biomarkers and Blood-brain Barrier Integritymentioning
confidence: 99%
“…The existing literature is not entirely consistent, however. Friis et al ( Friis et al, 2022 ) reported increased plasma concentrations of neurofilament light, tau, neuron-specific enolase, and S100B in women with preeclampsia compared to women who had normative pregnancies. Conflicting findings such as those related to S100B highlight the need for additional research regarding the underlying influences of cerebral biomarkers.…”
Section: Cerebral Biomarkers and Blood-brain Barrier Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that NfL could be a promising biomarker for BBB alterations in preeclampsia. 111…”
Section: Preclinical Studiesmentioning
confidence: 99%